Detection of neutrinos from micro-quasars i - Civitarese, Enrique Osvaldo (2012)
Using the neutrino intensity obtained from models for high-energy particle-emission from low-mass micro-quasars, we calculate the neutrino flux with and without including neutrino oscillations. We show that the neutrino flux from a micro-quasar is affected by neutrino oscillations. The effect reflects upon the increase in the time of observation, for km-scale neutrino detector. © 2012 World Scientific Publishing Company.